POLITENESS STRATEGIES IN EFL CLASSROOM INTERACTION: TEACHER-STUDENT STRATEGIES - Elis Jayanti, Nur; Mahmud, Murni; Salija, Kisman (International Journal of Business English and Communication, 2024)
This study explores the use of politeness strategies in English as a Foreign Language (EFL) classroom interactions, focusing on the dynamic between a teacher and four students at SMPN 2 Galesong Utara. Utilizing a descriptive qualitative mythological approach and ethnography design, data were gathered through observation checklists, interviews, and audio-video recordings. The research aims to answer three key questions: (1) The teacher's perception of politeness strategies, (2) The dominance of specific politeness strategies in teacher-student interactions, and (3) How politeness strategies support teacher and student classroom interaction. According to the teacher's perceptions, politeness is crucial for effective communication. She defines it as using respectful language that does not offend listeners. The finding of the most dominant implemented in the interaction of teacher-students in EFL classroom was positive politeness. The finding of how politeness strategies support teacher-students’ interaction was that politeness strategies are crucial in creating an inclusive and effective learning environment. They not only support harmonious teacher-student interactions but also facilitate better learning outcomes by ensuring respect and cooperation in the classroom.